Petrology and geochemistry of the Teluk Ramunia volcanics, southeastern Johor,Peninsular Malaysia; implication for middle triassic tectonic / Muhammad Hatta Bin Roselee - Roselee, Muhammad Hatta (2014)

(untitled)
The main objective of this study is to investigate the petrology, geochemistry and petrogenesis of volcanic rocks from southeast Peninsular Malaysia mainly within Teluk Ramunia. The volcanic rocks from that area are located on the eastern belt magmatism dominated by I-type rocks. The rocks from study area are dominated by rhyolite, trachydacite and diorite and they show irregular contact which suggests contemporaneous crystallization. Petrographically, all rocks shows occurrence of microgranophyric, interstitial biotite and hornblende which is characteristic of the Atype rocks and sub-volcanic emplacement. Field and geochemical evidence shows that the rhyolite is derived from a different magmatic pulse than trachydacite and diorite. The value of Ga/A and HFSE (Zr+Nb+Ce+Hf) for all rocks from study area is comparable to the average A-type rocks. All rocks shows range from metaluminous to weakly peraluminous in term of their A/CNK value. All rocks from Ramunia yield high zircon saturation temperature value (826+ 5oC) and high content of high field strength elements (e.x. Zr,Nb,Ce and Hf) which are clearly indicative of dry source derived or low pressure incongruent melting. Based on geochemical, petrographical and high saturation temperature and low pressure (~3.2kbar) calculated from thermometry shows that all Rock from Ramunia may plausibly derived from low pressure melting of granodiorite. Based on zircon U-Pb isotope age, rhyolite gave age about 238 + 2 Ma which suggest that all rocks are related to subduction of the Palaeo-tethys ocean underneath Indochina (volcanic arc). However the occurrences A-type give implication that all rocks are formed during crustal extension due to oceanic slab rollback. The under-plated mantle derived basalt will intrude into the lower to middle crust and provide sufficient heat to melt the country rocks. The high heat yield by the mantle derived basalt will contribute to the low pressure incongruent melting of the middle iv crust rocks (tonalite and granodiorite) which will formed the A-type magma and gradually crystallized to be Ramunia volcanics. It is high possible that there are more occurrence of the A-type rocks throughout Eastern belt province of Peninsular Malaysia.